2009
DOI: 10.1242/jcs.046441
|View full text |Cite
|
Sign up to set email alerts
|

Functional homology of mammalian syntaxin 16 and yeast Tlg2p reveals a conserved regulatory mechanism

Abstract: Membrane fusion in all eukaryotic cells is regulated by the formation of specific SNARE (soluble N-ethylmaleimide-sensitive factor attachment protein receptor) complexes. The molecular mechanisms that control this process are conserved through evolution and require several protein families, including Sec1p/Munc18 (SM) proteins. Here, we demonstrate that the mammalian SNARE protein syntaxin 16 (Sx16, also known as Syn16) is a functional homologue of the yeast SNARE Tlg2p, in that its expression fully complement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…5A, Stx6 and Vti1a could bind the immobilized GST-Stx16 but not GST. The presence of Vps45 enhanced their interactions (by 143610% for Vti1a and by 223612.3% for Stx6), consistent with previous reports (Struthers et al, 2009). Remarkably, the addition of Cog4 subunit further enhanced the binding of Vti1a and Stx6 to Stx16 (by 24068.5% and 400615%, respectively), suggesting that the Cog4 subunit facilitates tSNARE complex assembly.…”
Section: Cog4 Facilitates the Assembly Of Fusogenic Stx6 Snare Complexsupporting
confidence: 90%
See 1 more Smart Citation
“…5A, Stx6 and Vti1a could bind the immobilized GST-Stx16 but not GST. The presence of Vps45 enhanced their interactions (by 143610% for Vti1a and by 223612.3% for Stx6), consistent with previous reports (Struthers et al, 2009). Remarkably, the addition of Cog4 subunit further enhanced the binding of Vti1a and Stx6 to Stx16 (by 24068.5% and 400615%, respectively), suggesting that the Cog4 subunit facilitates tSNARE complex assembly.…”
Section: Cog4 Facilitates the Assembly Of Fusogenic Stx6 Snare Complexsupporting
confidence: 90%
“…We could reconstitute the assembly of Stx6-Stx16-Vti1a in the absence or presence of either Vps45 or Cog4, and showed that both Cog4 and Vps45 enhance tSNARE complex assembly. While the stimulatory effect of Vps45 on SNARE complex assembly has been previously shown (Struthers et al, 2009), the influence of Cog4 on tSNARE assembly is shown here for the first time. The entire COG complex, which can bind directly the three tSNAREs, might have an even stronger effect on tSNAREs assembly.…”
Section: Discussionsupporting
confidence: 55%
“…First, we previously showed that deletion of the first 230 residues of Tlg2p in vps45⌬ cells leads to endosomal SNARE complex formation (35), suggesting that in the absence of Vps45p, the closed conformation of Tlg2p inhibits SNARE complex assembly. Second, we have recently demonstrated that either removal of the Tlg2p H abc domain or the addition of Vps45p increases the rate of endosomal SNARE complex assembly in vitro (36). Here, we show that binding of Vps45p to the C-terminal binding site requires the H abc , linker and SNARE motif regions of Tlg2p.…”
Section: Discussionmentioning
confidence: 66%
“…This study gapped pNB701 as described previously (Struthers et al, 2009). pHA-G4/Gap1, the retroviral expression vector encoding HA-tagged human GLUT4 with the entire C-terminal cytosolic tail (residues 470-509; please see supplementary material Table S1) replaced with the analogous region of the yeast protein Gap1 (residues 547-602; please see supplementary material Table S1) was constructed using SOEing PCR to generate a GLUT4/GAP1 chimeric ORF as follows.…”
Section: Plasmidsmentioning
confidence: 99%